2014
DOI: 10.1126/science.1258106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the support on surface rearrangements of bimetallic nanoparticles in real catalysts

Abstract: Catalysts used for heterogeneous processes are usually composed of metal nanoparticles dispersed over a high-surface-area support. In recent years, near-ambient pressure techniques have allowed catalyst characterization under operating conditions, overcoming the pressure gap effect. However, the use of model systems may not truly represent the changes that occur in real catalysts (the so-called material gap effect). Supports can play an important role in the catalytic process by providing new active sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 31 publications
8
162
0
1
Order By: Relevance
“…These results agree with oxidation/reduction cycles (Section 2.4.1) and may result from a change in the distribution of oxygen vacancies on the catalytic surface promoted by reducing agents present in the reaction system [68]. Divins et al [46] evaluated a RhPd/CeO2 catalyst in the SRE, also reporting an increase in the Ce +3 /Ce +4 ratio from 0.63 to 0.83 after reaction at 550 °C. The authors suggested that the capability of CeO2 as a support to activate water and to donate oxygen atoms could oxidize noble metals in the SRE.…”
Section: Xpssupporting
confidence: 75%
See 1 more Smart Citation
“…These results agree with oxidation/reduction cycles (Section 2.4.1) and may result from a change in the distribution of oxygen vacancies on the catalytic surface promoted by reducing agents present in the reaction system [68]. Divins et al [46] evaluated a RhPd/CeO2 catalyst in the SRE, also reporting an increase in the Ce +3 /Ce +4 ratio from 0.63 to 0.83 after reaction at 550 °C. The authors suggested that the capability of CeO2 as a support to activate water and to donate oxygen atoms could oxidize noble metals in the SRE.…”
Section: Xpssupporting
confidence: 75%
“…In this way, some of the CO produced is converted to CO2 by the WGSR, which, as expected by thermodynamics, occurred to a lesser extent as the temperature increased (Table 1). Idriss et al [19] and Divins et al [46] evaluated RhPd/CeO2 catalysts in the SRE, reporting that the increase in H2 yield around 700 °C is due to simultaneous presence of WGSR and methane reforming.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the Ir-Pd system, energy dispersive X-ray (EDX) profiles of the biggest particles (*5 nm of diameter) showed a surface enrichment in Pd (Zlotea et al 2014), as predicted by our calculations (in the experiments, the sensitivity of the EDX detector was not sufficient to allow recording of concentration profiles for small particles). Under reaction conditions, the structure may actually evolve (Divins et al 2014).…”
Section: Preliminary Considerations On the Bulk Irpd Systemmentioning
confidence: 99%
“…To get insight into the structural characteristics of our RhPd/CeO 2 catalysts we have studied them by STEM and XRD under operando conditions. We have used operando XRD because we have recently shown that strong restructuring of the ceria-supported RhPd nanoparticles occurs under ESR conditions, which induces strong changes to the behavior of the catalyst [36]. about 15-25 nm in size and exhibiting abundant {1 1 1} crystallographic planes, as expected.…”
Section: Catalytic Performancementioning
confidence: 99%